Mold Infections of the Central Nervous System - McCarthy, Matthew (N Engl J Med, 2014)
The recent outbreak of exserohilum rostratum meningitis linked to epidural injections of methylprednisolone acetate has brought renewed attention to mold infections of the central nervous system (CNS).(1) Although uncommon, these infections are often devastating and difficult to treat. This focused review of the epidemiologic aspects, clinical characteristics, and treatment of mold infections of the CNS covers a group of common pathogens: aspergillus, fusarium, and scedosporium species, molds in the order Mucorales, and dematiaceous molds. Infections caused by these pathogen groups have distinctive epidemiologic profiles, clinical manifestations, microbiologic characteristics, and therapeutic implications, all of which clinicians should understand.